Structural equation modelling of customer attitudes towards social network advertising: a case of Iranian social networking site. (2017) - Mirmehdi, Seyyed Mehdi; Sanayei, Ali; Dolatabadi, Hossein Rezaei
At present, social networking sites have provided an appropriate context for advertisement. Previous studies have investigated the attitudes toward advertisement in the traditional media and on the internet; however, there has been little examination of attitudes towards social network advertising. The very aim of the present study is to investigate the influential factors affecting the attitudes towards social network advertising. To achieve this aim, a structural model was formulated to analyse and test the factors present among users of an Iranian social networking site. The results revealed that factors such as entertainment, product information, social image, good for the economy, credibility, interactivity, materialism, and value corruption affect the attitudes towards social network advertising while the factor of irritation is not influential.